Culture, power, and the state ideology - Wan Mohd Ghazali, Wan Norshira (2018)
This paper aims at establishing relationships between culture, power, and the state ideology. The reading of Malaysian politics through Gramsci’s conceptual framework provides a tentative interpretation on the state’s exercise of power with popular consent, the structure of power, relation between the state and subaltern groups. Reading through Gramsci’s theory of hegemony, the paper explores the construction and enactment of Islam by the power of the state. It highlights how Islam came to be constructed as the state ideology and how the state establishes and maintains the hegemonic strategy. On this basis, Islam has been used to produce a specific set of hegemonic structures in Malaysia to gain national-popular support. Further, the state-society relations will be explored through Gramsci’s notion of civil society to illustrate the possible resistance to the state hegemony. The paper suggests that civil society as a field of contestations in Malaysia. The 14th General Election result has demonstrated that ideology could be contested, hence challenging the state’s domination or coercive power.